Chinese tourists' perceptions of front office service levels in New Zealand budget hotels (3 star) - Wang, Hui (Auckland University of Technology, 2006)
This report is in an attempt to probe the significance of distinctive cultures towards to the hotel operations. As with the incremental demands of Chinese inbound tourism to New Zealand, it is essential that New Zealand local budget hotels are required to provide a standardized level of service to satisfy diverse customers with necessary concerns on their different cultural backgrounds. This dissertation is based upon a well-designed quantitative survery, which carried out by a Master student of International Hopitality Management. The objectives of the research are to try to provide an extensive and in-depth analysis of the characteristics of group Chinese tourists, to elicit and analyze qualitatitve data based on the survey instrument, to identify any gaps between the Chinese tourist expectation and their perception of front office service levels, and to generate new knowledge concerning Chinese tourist behaviour. The findings of the study revealed that current Chinese inbound tourists have distinctive behaviour, which is one of the main problems leading to most disappointing service perceptions in budget hotels. The study also implied that cultural difference could be one of the significant variables moderate service levels in the hospitality domain, and that front office played a most important role as the cultural service performer to deal with the international market.
Keywords: Hotels -- Customer services -- New Zealand; Tourists -- New Zealand; Chinese -- Travel